2019
DOI: 10.5433/1679-0359.2019v40n2p555
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of water erosion by the erosion potential method in a pilot subbasin in southern Minas Gerais

Abstract: Soil losses due to water erosion threaten the sustainability of agriculture and the food security of current and future generations. This study estimated potential soil losses and sediment production under different types of land uses in a subbasin in the Municipality of Alfenas, southern Minas Gerais, southeastern Brazil. The objective of this research was to evaluate the application of the Potential Erosion Method by the Intensity of Erosion and Drainage program and correlate the findings with the results ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 32 publications
3
19
1
8
Order By: Relevance
“…The observed mean was close to that found by Mendes Júnior et al (2018), which evaluated the potential soil losses with the RUSLE method in the same region obtained a value of 1.52 Mg ha -1 year -1 . The data also agree with the results obtained by Tavares et al (2019), who observed losses of 1.46 Mg ha -1 year -1 using EPM. The proximity of the results with the values of the literature indicates precision and reliability in the estimation performed by the method.…”
Section: Land Use Classessupporting
confidence: 91%
See 4 more Smart Citations
“…The observed mean was close to that found by Mendes Júnior et al (2018), which evaluated the potential soil losses with the RUSLE method in the same region obtained a value of 1.52 Mg ha -1 year -1 . The data also agree with the results obtained by Tavares et al (2019), who observed losses of 1.46 Mg ha -1 year -1 using EPM. The proximity of the results with the values of the literature indicates precision and reliability in the estimation performed by the method.…”
Section: Land Use Classessupporting
confidence: 91%
“…The parameters used in the T calculations are present in table 4. The T values corroborate with the results found by Tavares et al (2019) for a dystrophic Red Latosol in the south of Minas Gerais. However, Cândido et al (2014) studying a dystrophic Red Latosol in the Mato Grosso do Sul State found values of 9 to 10 Mg ha -1 year -1 .…”
Section: Land Use Classessupporting
confidence: 89%
See 3 more Smart Citations